Community-development programs and the implications for women migrant workers’ pre-departure preparation in eastern Indonesia - Metboki, Yakob; Ledo, Jolly Petrecia Hosang (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2019)
This paper aims to describe the implementation of the community development programs and the benefits originated from the prospective women migrant workers’ responses after taking the training. The problems are